Algebra and Coalgebra in Computer Science Third International Conference, CALCO 2009, Udine, Italy, September 7-10, 2009. Proceedings - Kurz, Alexander.; Lenisa, Marina.; Tarlecki, Andrzej. (Lecture Notes in Computer Science, 2009)
This book constitutes the proceedings of the Third International Conference on Algebra and Coalgebra in Computer Science, CALCO 2009, formed in 2005 by joining CMCS and WADT. This year the conference was held in Udine, Italy, September 7-10, 2009. The 23 full papers were carefully reviewed and selected from 42 submissions. They are presented together with four invited talks and workshop papers from the CALCO-tools Workshop. The conference was divided into the following sessions: algebraic effects and recursive equations, theory of coalgebra, coinduction, bisimulation, stone duality, game theory, graph transformation, and software development techniques.